Cost Coordination. - Harrington, Joseph E. (RAND Journal of Economics (Wiley-Blackwell))
In markets with price discrimination, firms can face a trade‐off when colluding. To maintain price discrimination, upper‐level executives may have to involve lower‐level employees with the requisite demand information but that enhances the risk of the cartel's discovery. They could instead centralize pricing authority, but that means less price discrimination. Here, we consider a third option, which is for executives to coordinate on inflating the cost used in pricing by lower‐level employees. Coordinating cost reports is shown to be more profitable than coordinating prices when market heterogeneity is sufficiently great or firms' products are sufficiently differentiated.